Efeito da terapia Reiki sobre os índices da variabilidade da frequência cardíaca em pacientes diabéticos - Canella, Glauco César da Conceição [UNESP]; Quitério, Robison José [UNESP]; Catai, Aparecida Maria [UNESP]; Chagas, Eduardo Federighi Baisi; Valente, Vitor Engrácia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Evidence on the clinical and physiological effects of bioenergetic therapies lack of scientific studies, particularly those that analyze the risk factors for epidemic diseases such as diabetes. Objectives: To investigate the acute effects of therapeutic intervention Reiki on heart rate variability in individuals between 58 to 75 years with diabetes mellitus type 2. Methodology: A total of 7 individuals of both sexes, aged between 58 and 75 years, type 2 diabetes mellitus Reiki was applied for 50 minutes at this stage were performed the registration of HR and R-R intervals (R-Ri) and calculated indexes of heart rate variability (HRV) in time domain and frequency. Results: The HRV indexes showed no significant differences between the rest condition, placebo and Reiki, to points 1, 2, 3 and 4 (p> 0.05). Conclusions: The application of Reiki do not change the temporal and spectral indices of cardiac autonomic modulation.

Evidências sobre os efeitos clínicos e fisiológicos das terapias bioenergéticas carecem de estudos científicos, particularmente as que analisem os fatores de risco para as doenças epidêmicas como o Diabetes. Objetivos: Investigar os efeitos agudos da intervenção terapêutica Reiki sobre a variabilidade da frequência cardíaca, em indivíduos entre 58 a 75 anos que apresentam diabetes mellitus do tipo 2. Metodologia: Foram estudados 7 indivíduos de ambos sexos, com idades entre 58 e 75 anos, com diabetes mellitus tipo 2. O Reiki foi aplicado por 50 minutos, nesta etapa foram realizados o registro da FC e dos intervalos R-R (iR-R) e calculados os índices de variabilidade da frequência cardíaca (VFC) no domínio do tempo e da frequência. Resultados: Os índices VFC não apresentaram diferenças significativas entre a condição de repouso, placebo e Reiki, para os pontos 1, 2, 3 e 4 (p>0,05). Conclusões: A aplicação de Reiki não alteram os índices temporais e espectrais da modulação autonômica cardíaca.
Keywords: Autonomic nervous system; Heart rate variability; Diabetes mellitus; Sistema nervoso autonômico; Variabilidade da frequência cardíaca; Diabetes mellitus